The Scientific Plus - Student Worksheet Development on Exposition Writing Text Learning to Improve the Students’ HOTS - Sagitari, Wulanti; Purnomo, Mulyadi Eko; Ernalida, Ernalida (Journal of Education Research and Evaluation, 2021)
Professional educators should be able to develop teaching materials to cope with the 2013 curriculum learning objectives in any given learning circumstances. Their preparedness to carry out the teaching-learning process could be assisted by applying teaching materials that are in line with the 2013 curriculum. This research aims to conduct a need analysis survey from various research stages and development stages to develop and validate the product and to determine what kind of teaching materials. The applied stages of a research and development study consist of (1) instructional process identification, (2) the analysis of the targeted learning outcomes, and (3) the analysis of the learners and their needs. The research location was in Public Senior High School 3 Prabumulih, Southern Sumatera Province. The subjects consisted of tenth graders with a population of 185 learners and 2 Indonesian language teachers. The numbers of the sample were 28 learners or 15% of the population. The first technique to collect the data was a questionnaire of the learners’ needs and the interview. Based on the findings and discussion, the recommended student worksheet by the researchers was an exposition-student worksheet with a scientific plus approach. With this student worksheet, the learners could train their skills and seek accurate information to be expressed in their exposition text. On the other hand, the teachers could also monitor and facilitate the learners to construct their knowledge about the text.